ATTITUDE AS A NEW MEDIA DISCOURSE INSTRUMENT AND ITS IMPACT ON YOUNG PEOPLE’S CONSCIOUSNESS IN THE DIGITAL AGE - Guslyakova, Alla; Guslyakova, Nina; Kirsanov, Vyacheslav; Valeeva, Nailya; Veretennikova, Lyudmila; Vetkhova, Marina (Revista Inclusiones, 2020)
The purpose of this research is to analyze the phenomenon of psychological attitude and its effect on the development of young people’s consciousness and their worldview. The correlation, cluster and factor analyses allowed identifying multiple positive correlations between young people’s interaction with the new media discourse and various attitudes perceived on different events, people and news and explaining inner reasons why the youth may respond to a certain piece of information in the media discourse and completely ignore another one.